2010
DOI: 10.1155/2010/213960
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Exposures to Particulate Matter and Carbon Monoxide during Ethiopian Coffee Ceremonies in Addis Ababa: A Pilot Study

Abstract: The unique Ethiopian cultural tradition of the coffee ceremony increases inhalation exposures to combustion byproducts. This pilot study evaluated exposures to particulate matter and carbon monoxide in ten Addis Ababa homes during coffee ceremonies. For coffee preparers the geometric mean (57 μg/m3) and median (72 μg/m3) contributions to an increase in a 24-hour time-weighted average exposure were above World Health Organization (WHO) guidelines. At 40% of the study sites the contribution to the 24-hour averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 5 publications
2
29
0
Order By: Relevance
“…Presence of extra indoor burning events, such as coffee ceremony, burning incense and local alcohol/" areqi" making in the household, was associated with more than two-fold increase in the odds of suffering from childhood ALRI with an estimated AOR of 2.19 (95% CI:1.41-3.40) when compared with no extra indoor burning event. This might be due to an increase in indoor particulate matter concentration as stated by a pilot study conducted among coffee ceremony participants in Addis Ababa homes which reported that the Ethiopian coffee ceremony inside houses could increase the concentration of HAP [50]. The most important inference of this finding is that HAP exposure from extra indoor burning events such as coffee ceremony, burning incense and local alcohol/"areqi" making in the household might elevate the odds of suffering from ALRI in children and this should be further investigated to estimate the separate childhood risks and recommend possible interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of extra indoor burning events, such as coffee ceremony, burning incense and local alcohol/" areqi" making in the household, was associated with more than two-fold increase in the odds of suffering from childhood ALRI with an estimated AOR of 2.19 (95% CI:1.41-3.40) when compared with no extra indoor burning event. This might be due to an increase in indoor particulate matter concentration as stated by a pilot study conducted among coffee ceremony participants in Addis Ababa homes which reported that the Ethiopian coffee ceremony inside houses could increase the concentration of HAP [50]. The most important inference of this finding is that HAP exposure from extra indoor burning events such as coffee ceremony, burning incense and local alcohol/"areqi" making in the household might elevate the odds of suffering from ALRI in children and this should be further investigated to estimate the separate childhood risks and recommend possible interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of extra indoor burning events, such as coffee ceremony, burning incense and local alcohol/ "areqi" making in the household, was associated with more than two-fold increase in the odds of suffering from childhood ALRI with an estimated AOR of 2.19 (95% CI:1.41-3.40) when compared with no extra indoor burning event. This might be due to an increase in indoor particulate matter concentration as stated by a pilot study conducted among coffee ceremony participants in Addis Ababa homes which reported that the Ethiopian coffee ceremony inside houses could increase the concentration of HAP (51). The most important inference of this finding is that HAP exposure from extra indoor burning events such as coffee ceremony, burning incense and local alcohol/"areqi" making in the household might elevate the odds of suffering from ALRI in children and this should be further investigated to estimate the separate childhood risks and recommend possible interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the logistical reasons, it was not possible to calibrate the instruments during or after the experiment. We therefore relied on calibration data from the manufacturer, which have been confirmed to be reliable with calibration checks outside the factory in a similar study (Keil et al., 2010). To provide reassurance in the measurements obtained, we assessed the precision of the CO logger measurements by the use of duplicates in 10% of the households, and by co‐locating all the 12 CO loggers used in the study for 48‐h period in three separate tests.…”
Section: Methodsmentioning
confidence: 99%